A novel cementitious microfiltration membrane: mechanisms of pore formation and properties for water permeation. Issue 1 (1st December 2014) - Wang, Zhe; Chen, Zhonglin; Chang, Jing; Shen, Jimin; Kang, Jing; Yang, Lei; Chen, Qian
Abstract : A low-cost cementitious inorganic membrane, with mean pore size of 2.4 μm, was fabricated under ambient conditions. Abstract : This study involved the fabrication of a novel low-cost microfiltration membrane using quartz and cement. The entire fabrication process was conducted at room temperature, rather than utilizing high-temperature sintering, as is generally done during the fabrication of traditional inorganic membranes. The mean pore size of the membrane ranged from 0.4 to 2.4 μm depending on the quartz-to-cement ratio ( q / c ) used. Two types of pores (I and II) were formed in the membrane. The formation of type I pores was mainly attributed to the stacking of cement particles. The formation of type II pores, which were less prevalent than type I pores, was attributed to the division of bigger pores by the thin needle-like ettringite. The sizes of the type I and type II pores varied significantly, depending on the used q / c . Moreover, investigation of the membrane properties showed that as the q / c used increased, increases were obtained for both the membrane porosity (from 18.4% to 31.4%) and water flux (from 0.16 to 13.26 m 3 m −2 h −1 bar −1 ), whereas the bending strength decreased (from 9.75 to 3.54 MPa). Additionally, element dissolution experiments demonstrated that the membrane was suitable for use for water treatment.